Parâmetros ultrassonográficos e dopplerfluxométricos renais de coelhos jovens e fêmeas adultas da raça mini Lionhead - Querino, Dallyana Roberta dos Santos (2020)
Over the years, Brazil has been arousing interest in the development of rabbit farming through the breeding of pet rabbits, highlighting several breeds used for this purpose, among them the mini Lionhead, Fuzzy lop, Mini lop and Netherland Dwarf. The Lionhead or mini Lionhead, which has a pet purpose, is a breed very searched due its anatomical characteristics. Renal failure is rare in rabbits. Renal lesions are seen more frequently in elderly animals. Symptoms include apathy, anorexia and polyuria and polydipsia. Changes in biochemical parameters are similar to those observed in domestic carnivores, with an increase in urea and creatinine values. Ultrasonography, as a method of diagnostic imaging, allows the evaluation and diagnosis of anatomical and pathological changes, as well as the monitoring of therapeutic evolution. There are still few studies carried out in this species, with no normal pattern for several parameters, including renal doppler flowmetry. The objective of this work was to describe the ultrasound parameters of the renal parenchyma and standardize the dopplerfluxometric values of young and adult Mini Lionhead rabbits. Thirty healthy Mini Lionhead rabbits were used, weighing between 0.48 grams and 1.98 kilograms, from the Cuniculture sector of the Federal University of Paraiba. The animals were divided into two distinct groups, young animals up to 2 months old (G1, 11 animals) and adult females up to 2 years old (G2, 19 animals). Portable ultrasound equipment with a convex transducer (8 - 12 MHz) was used. The animals were evaluated in dorsal or lateral decubitus position. Images of the kidneys were obtained through longitudinal, coronal and transverse sections in B mode, with a morphological evaluation and measurement of the height, width and thickness and renal volume. The kidneys had a bean shape, defined edges, preserved corticomedullary relationship and homogeneous echotexture in both young and adults animals. The echogenicity of the cortical of the left kidney was hypoechoic when compared to the spleen and the right kidney was isoechoic and slightly hyperechoic when compared to the liver. In young animals, the right kidney was only isoechoic in relation to the liver. There was a positive correlation (p <0.05) between body weight, length measurements, width measurements, thickness measurements and right and left renal volume. The dopplerfuxometric values of the arched arteries were significantly higher in the right and left kidneys in animals of G2 when compared to G1 (p <0.05). In the group of young animals, the mean RI of the arched arteries was 0.44 ± 0.05 for the left kidney and 0.44 ± 0.05 for the right kidney, while in the adult group, 0.55 ± 0.07 for the left kidney and 0.56 ± 0.07 for the right kidney. Knowledge of these parameters will help in the diagnosis of kidney pathologies in rabbits, since these animals are being introduced more frequently in the family, increasing their longevity and with increasing age, common diseases appear to the elderly, such as kidney disease.